International PKM Model to Encourage Campus Entrepreneurship through ASEAN Cooperative Collaboration - Diapepin, Mukti; Jamilah; Salfadri; Gus Andri; Silfia Rini; Febriyeni; Cory Febrina; Sari Gando Hidayati (Journal of Community Service and Application of Science, 2025)
The international Community Partnership Program (PKM) is an effort to enhance globally competitive campus entrepreneurship. The purpose of this community service program is to discuss the international PKM model based on cooperative collaboration in the ASEAN region, with a focus on the exchange of best practices, cooperative digitalization, and the development of student entrepreneurship-based business units. Activities were carried out through literature studies, field observations at partner cooperatives in Malaysia (ANGKASA), and capacity building workshops for university cooperative managers. The results indicate that cross-border collaboration can strengthen cooperative business networks, encourage the emergence of adaptive campus entrepreneurship models, and expand market access for student products. This article offers a framework for the international PKM model that can be replicated at other universities in Indonesia to accelerate the internationalization of campus cooperatives. This approach not only improves student business literacy but also expands business networks and innovation across countries. The research used a descriptive qualitative method with a case study approach on collaboration between student cooperatives in Indonesia and Malaysia. The results indicate that cross-border collaboration in the form of joint entrepreneurship training, business incubation, and the transfer of digital cooperative practices has a significant impact on increasing student entrepreneurial interest and capacity. This model is recommended as a leading PKM program integrated with the Independent Learning and Independent Campus (MBKM) policy and the ASEAN economic integration agenda.